(untitled) (Journal of Music Research Online, 2022)
This paper investigates spacetime and auditory sense in the context of the American composer and sound artist Pauline Oliveros and that of French philosopher Gilles Deleuze. For both thinkers a radical empirical engagement with sensation produces a suite of concepts foreground the immanence of experience, in particular, the radical particularity of embodied encounter between bodies, spaces, and sonic events. Building the structure of encounter through primarily Deleuzian terms, disrupting sedentary binaries, affirming a sense prior to language, and tracing the conditions of sonorous becoming, a concept emerges of the spacetime of sense and sensory objects released from the control of the mediation of the Western Image of Thought.